2020
DOI: 10.3390/genes11101186
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Classification, Characterization, and Expression Analysis of the Wall-Associated Kinase Family during Fruit Development and under Wound Stress in Tomato (Solanum lycopersicum L.)

Abstract: The wall-associated kinase (WAK) and wall-associated kinase like (WAKL) is a subfamily of receptor-like kinases associated with the cell wall, which have been suggested as sensors of the extracellular environment and triggers of intracellular signals. However, these proteins have not yet been comprehensively analyzed in tomato (Solanum lycopersicum L.). In this study, 11 SlWAK and 18 SlWAKL genes were identified in an uneven distribution in 9 of 12 chromosomes. GUB-WAK-bind (wall-associated receptor kinase gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Phylogenetic analysis shows that these members can be divided into five clades ( Figure 1 ). Previous phylogenetic studies on WAK/WAKL proteins in cotton [ 7 ], tomato [ 34 ], barley [ 25 ] and other plants have found that these proteins tend to form species-specific clades. The most WAK/WAKL proteins in Arabidopsis clustered in the same group compared with other species [ 7 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analysis shows that these members can be divided into five clades ( Figure 1 ). Previous phylogenetic studies on WAK/WAKL proteins in cotton [ 7 ], tomato [ 34 ], barley [ 25 ] and other plants have found that these proteins tend to form species-specific clades. The most WAK/WAKL proteins in Arabidopsis clustered in the same group compared with other species [ 7 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous phylogenetic studies on WAK/WAKL proteins in cotton [ 7 ], tomato [ 34 ], barley [ 25 ] and other plants have found that these proteins tend to form species-specific clades. The most WAK/WAKL proteins in Arabidopsis clustered in the same group compared with other species [ 7 , 34 , 35 ]. The phylogenetic relationships of five species (Arabidopsis, G. hirsutum , Q. robur , J. regia and J. mandshurica ) also showed that the WAK/WAKL proteins clustered into species-specific clades, especially Arabidopsis and G. hirsutum ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Characterizing the WAK gene family will help identify many new candidate genes that may contribute to disease resistance. Presently, WAK gene families have been identified and characterized in diverse plant species, including 26 members in Arabidopsis [3], 125 in rice [27], 91 in barley [28], 27 in walnuts [29], 29 in tomato [25], 29 in potato [36], and 29 in cotton [26]. Although several wheat WAKs have been reported, their genome-wide characterization in the complicated wheat hexaploid genome is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Genome sequences can provide valuable information for genome-based investigations. To date, the WAK gene family has been comprehensively identified in various plant species such as Arabidopsis [3], tomato [25], cotton [26], rice [27], barley [28], and walnuts [29]. However, systematic investigations of WAKs are yet to be performed in the wheat genome.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Recently, genome-wide analysis and characterization of the WAK/WAKL gene family has been reported for many other plant species including tomato ( Solanum lycopersicum ) and cotton ( Gossypium hirsutum ). 6 , 7 …”
Section: Introductionmentioning
confidence: 99%